Seasonal variations in healthcare-associated infection in neonates in Canada. Issue 1 (3rd May 2012) - Shah, Prakesh S; Yoon, Woojin; Kalapesi, Zarin; Bassil, Kate; Dunn, Michael; Lee, Shoo K
Abstract : Objective: To assess the seasonal pattern of healthcare-associated infections (HCAI) among neonates and to describe the trend of HCAI. Design: Secondary analyses of database. Setting: The Canadian Neonatal Network database (2003–2009). Participants: Neonates with HCAI defined as blood/cerebrospinal fluid positive with pathogenic organism in a symptomatic infant after 2 days of age. Main outcome measure: The incidence rate for HCAI per 1000 days with a 95% CI, for the 4 warmest months (June–September) was compared with the remaining 8 months, to calculate the incidence rate ratio (IRR). Results: Of 75 629 total infants, 4305 (5.7%) had HCAI (3367 had 1 and 938 had >1 episodes). Infants who had HCAI were of lower gestation, birth weight and Apgar score; but had higher severity of illness scores and clinical chorioamnionitis. There was a borderline increase in all HCAI (IRR 1.05, 95% CI 1.00 to 1.11) and a significant increase in Gram-negative HCAI (IRR 1.20, 95% CI 1.04 to 1.39) during the summer months. Overall, there was a 20% reduction in HCAI from 4.45/1000 days in January 2003 to 3.54/1000 days in December 2009 (mean difference 0.91/1000 days (95% CI 0.89 to 0.92). Conclusions: Gram-negative infections were significantly increased during the summer months of the year compared with the rest of the year among neonates. Overall, there was a significant temporal reduction in HCAI rates over the study period.